The DMF-T Index and Its Association with Preeclampsia in Pregnant Women at the Wonoayu Health Center - Dayanti, Marisa Elvi; Cholifah, Siti; Ashari, Tontowi (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Preeclampsia is a pregnancy-specific condition marked by hypertension and proteinuria after 20 weeks of gestation, posing risks to both mother and fetus. Poor oral health, indicated by a high DMF-T (Decayed, Missing, and Filled Teeth) index, may contribute to adverse pregnancy outcomes. Objective: To analyze the relationship between the DMF-T index and preeclampsia incidence in pregnant women. Methods: A cross-sectional study was conducted on 81 pregnant women selected through simple random sampling from a population of 417 who received antenatal care at Wonoayu Health Center in 2023. Data from dental and maternity records were analyzed using chi-square tests (a < 0.05). Results: Among respondents, 4 preeclampsia cases were found in the good DMF-T category and 13 in the poor DMF-T category. Statistical analysis showed a significant relationship between DMF-T index and preeclampsia (p = 0.000). Conclusion: Poor dental health, as reflected by a high DMF-T index, is significantly associated with preeclampsia in pregnant women. Strengthening oral health care and further research on its role in pregnancy outcomes are recommended.